![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
x2-4x-21
=x2-4x+4-25
=(x-2)2-52
=(x-2-5)(x-2+5)
=(x-7)(x+3)
A=\(x^2-4x-25+4\)
A= \(\left(x-2\right)^2-5^2\)
A=\(\left(x-2-5\right)\left(x-2+5\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^4+2019x^2+2018x+2019\)
\(=x^4-x^3+x^3+2019x^2-x^2+x^2+2019x-x+2019\)
\(=\left(x^4-x^3+2019x^2\right)+\left(x^3-x^2+2019x\right)+\left(x^2-x+2019\right)\)
\(=x^2\left(x^2-x+2019\right)+x\left(x^2-x+2019\right)+\left(x^2-x+2019\right)\)
\(=\left(x^2+x+1\right)\left(x^2-x+2019\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^{16}+x^8-2=x^{16}-x^8+2x^8-2=x^8\left(x^8-1\right)+2\left(x^8-1\right)\)
\(=\left(x^8+2\right)\left(x^8-1\right)=\left(x^8+2\right)\left(x^4+1\right)\left(x^4-1\right)\)
\(=\left(x^8+2\right)\left(x^4+1\right)\left(x^2+1\right)\left(x^2-1\right)\)
\(=\left(x^8+2\right)\left(x^4+1\right)\left(x^2+1\right)\left(x+1\right)\left(x-1\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có:\(x^3+9x^2+11x-21\)
\(=x^3-x^2+10x^2-10x+21x-21=x^2\left(x-1\right)+10x\left(x-1\right)+21\left(x-1\right)\)
\(=\left(x^2+10x+21\right)\left(x-1\right)=\left(x^2+3x+7x+21\right)\left(x-1\right)\)
\(=\left[x\left(x+3\right)+7\left(x+3\right)\right]\left(x-1\right)\)
\(=\left(x+3\right)\left(x+7\right)\left(x-1\right)\)
x^3+9x^2+11x-21=x^3-x^2+10x^2-10x+21x-21=(x^3-x^2)+(10x^2-10x)+(21x-21)
=x^2(x-1)+10x(x-1)+21(x-1)=(x-1)(x^2+10x+21)=(x-1)(x^2+3x+7x+21)=(x-1)[(x^2+3x)+(7x+21)]
=(x-1)(x+7)(x+3)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(m^2-16+n^2-2mn\)
\(=n^2-2mn+m^2-16\)
\(=\left(n-m\right)^2-16\)
\(=\left(n-m-4\right)\left(n-m+4\right)\)
m2 - 16 + n2 - 2mn
= m2 - 2mn + n2 - 16
= (m - n)2 - 42
= (m - n - 4)(m - n + 4)
![](https://rs.olm.vn/images/avt/0.png?1311)
x^3-9x^2+6x+16
=x^3+x^2-10x^2-10x+16x+16
=(x^3+x^2)-(10x^2+10x)+(16x+16)
=x^2(x+1)-10x(x+1)+16(x+1)
=(x+1)(x^2-10x+16)
=(x+1)(x^2-2x-8x+16)
=(x+1)[(x^2-2x)-(8x-16)]
=(x+1)[x(x-2)-8(x-2)]
=(x+1)(x-2)(x-8)
đề xuất bình phương đủ